Tinjauan Yuridis Pembatalan Perkawinan Akibat Larangan Perkawinan Sedarah (Soghe Sala) Menurut Hukum Adat Nginamanu, Kecamatan Wolomeze, Kabupaten Ngada - Ndari, Eusabius; Hedewata, Agustinus; Mauritsius, Darius (Law Faculty, Nusa Cendana University, 2023)
Cancellation of consanguineous marriages ( Soghe Sala ) in marriage cases in Nginamnu Village, Wolomeze District, Ngada Regency. Case of Consanguineous Marriage ( Soghe Sala ) It was recorded that this happened frequently and was successfully resolved with the final solution, namely driving the two perpetrators out of Nginamnu Village. The formulation of the problem in the research is: (1) What is the process of annulment of an original marriage (Soghe sala) according to Nginamnu customary law Wolomeze District, Ngada Regency? (2) What are the consequences of the prohibition of consanguineous marriages (Soghe sala) according to Nginamanu Customary Law, Wolomeze District, Ngada Regency? This research is empirical, meaning that analyzing the problem is carried out by combining legal materials obtained in the field, legal sources and materials used, namely primary, secondary and tertiary legal materials and the data is analyzed descriptively qualitatively. The results of the research show: (1) Process for Cancellation of Consanguineous Marriage (Soghe sala) According to Nginamanu Customary Law: Lii Ve (Circulation of the Soghe Sala Issue), Gae Lara (Search for Solutions), Robo Koli (Ritual of Cutting Palm Leaves), Lara Eko (Final Solution ), and Gae Lara Wali (Looking for Other Solutions) Wolomeze District, Ngada Regency. (2) As a result of the Prohibition of Consanguineous Marriages (Soghe sala), violating this rule by carrying out clan marriages believes that a disaster will occur, namely a long drought and plantation crops will be damaged, the community will experience a long period of famine and the community will still respect the customary rules that have been established. Created a long time ago by previous ancestors, will be given the sanction of being ostracized or even expelled from the local area because the local community is afraid of a disaster that will occur in the area according to the Nginamanu Customary Law, Wolomeze District, Ngada Regency. In this case, the author suggests that parents educate their children from an early age to understand the traditional rules and traditional traditions in Nginamanu Village , so that when they grow up, those who are going to get married can choose a life partner who does not conflict with the traditional rules of Nginamanu Village and for traditional leaders. Nginamanu Village in every village must always provide traditional understandings, especially the prohibition on marriage within the clan, for prospective brides and grooms in the Karo community to marry according to religion, traditional customs, and also be registered with the authorized agency in accordance with the Marriage Law